1997
DOI: 10.1023/a:1008634632501
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: An elevated plasma homocysteine level may result from various environmental and genetic factors. Herediatary causes of severe hyperhomo-cysteinaemia are very rare and usually lead to disease in childhood or adolescence. Common pathology consists of early atherosclerotic vascular changes, arterioocclusive complications and venous thrombosis. Mildly elevated genetically determined plasma homocysteine levels are observed in 5% of the general population. In the last two decades research has shown mild hyperhomocys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…Our data suggest that MTHFR C677T genotype alone does not increase risk for postpartum psychopathology. Our findings are also broadly in line with previous studies that have shown that low folate (and thus subsequent high levels of homocysteine) is associated with various forms of psychopathology [56][57][58][59]. However, our findings suggest that this inverse relationship may only exist in the postpartum for women with a MTHFR C677T C allele, at least in terms of mania, and, perhaps, depressive symptoms.…”
Section: Plos Onesupporting
confidence: 92%
“…Our data suggest that MTHFR C677T genotype alone does not increase risk for postpartum psychopathology. Our findings are also broadly in line with previous studies that have shown that low folate (and thus subsequent high levels of homocysteine) is associated with various forms of psychopathology [56][57][58][59]. However, our findings suggest that this inverse relationship may only exist in the postpartum for women with a MTHFR C677T C allele, at least in terms of mania, and, perhaps, depressive symptoms.…”
Section: Plos Onesupporting
confidence: 92%
“…Because transsulfuration pathway/methionine cycle constituents can be impacted by nutritional interventions that alter vitamin B6 [57], choline, and cysteine [58], or methionine [59], our findings imply that in vivo dietary modalities may ultimately be designed to attenuate the potential epigenetic impact of oxidant stress. This may also contribute to our understanding of how diets rich in heme iron, which could be a strong source of dietary oxidant stress, may be linked to breast carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The Effect of C677T polymorphism in MTHFR enzyme activity was already studied and reported ( 27 , 29 , 30 ), however, a few studies have been done on A1298C polymorphism in our population to date. It already has shown that hyperhomocysteinemia and homozygous for MTHFR gene polymorphism, are risk factors for spontaneous abortion, whereas some researchers have rejected the relation between MTHFR polymorphisms and recurrent miscarriage ( 31 - 33 ).…”
Section: Discussionmentioning
confidence: 99%